Design research on learning and thinking in educational settings : enhancing intellectual growth and functioning - Dai, David Yun. (New York : Routledge, 2012)
'The key question this book addresses is how to identify and create optimal conditions for the kind of learning and development that is especially important for effectively functioning in the 21st century. Taking a new approach to this long-debated issue, it looks at how a design research-based science of learning (with its practical models and related design research) can provide insights and integrated models of how human beings actually function and grow in the social dynamics of educational settings with all their affordances and constraints. More specifically: How can specific domains or subject matters be taught for broad intellectual development? How can technology be integrated in enhancing human functioning? How can the social organization of classroom learning be optimized to create social norms for promoting deep intellectual engagement and personal growth? Part I is concerned with broad conceptual and technical issues regarding cultivating intellectual potential, with a focus on how design research might fill in an important a niche in addressing these issues. Part II presents specific design work in terms of design principles, models, and prototypes'-- Provided by publisher.
Includes bibliographical references and indexes.
Keywords: Cognitive learning; Learning, Psychology of; Critical thinking -- Study and teaching